SWOT ANALYSIS OF ERICULURE - Vaidya, Shubhangi (International Journal of Research -GRANTHAALAYAH, 2015)
The reduction of rural poverty continues to be a paramount goal of the developing countries like India. So far various strategies (Sericulture is most appropriate out of them) have been pursued to address this concern and the rural employment creation is one of the major aspects. In India Sericulture is essentially village based industry providing employment to a sizable section of a population. Sericulture is not only a traditional, but also a living culture. It is an agro based labour intensive and commercially attractive economic activity falling under the cottage and small scale sector. India is the largest producer of Eri silk in the world as 96% of Eri silk is produced in India of the total Eri silk produced in the world (Rajesh Kumar and S.K.Gangwar 2010). Ericulture cannot progress unless it is thought out, planned and implemented in total perspective of the nation. No doubt, the central as well as the state government have their agencies in many places of the country and have been doing something. The aim of my SWOT analysis is to develop work plan for my research that takes into consideration many different internal and external factors and maximizes the potential of the strengths and opportunities while seeking minimize the impact of the weaknesses and threats.